The Impact Of Village-Owned Enterprises (Bumdes) In Strengthening Local Economy In The Border Village Of Sebente, Bengkayang Regency - Blasius Manggu; Sabinus Beni (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
In an effort to improve the welfare of the community as a non-governmental organization and see the potential it has, as well as the needs of the community, the presence of "SETANGA LESTARI" BUMDES in Sebente Village Teriak District is the government's support in the effort to empower rural communities for a better life. The purpose of this research is to find out the role of Village-Owned Enterprises (BUMDES) in efforts to improve the local economy, knowing what the problems and obstacles faced by the Village-Owned Enterprises, in Sebente Village, Teriak District, Bengkayang Regency. Descriptive qualitative research, with various stages including finding literature that is in accordance with the problem and the topic in accordance with the object to be studied, field observations, permission to related parties to complete the instrument until the completion stage, the data is analyzed, and the next stage the data is reduced, then validated so that research is perfect. The results of the study concluded that the BUMDES had not yet had a positive impact on improving the welfare of the village community, as there were still some people in the preprosperous category.